READING ABILITY OF SENIOR AIR TRAFFIC CONTROL CADETS AS MEASURED BY ICAO ENGLISH LANGUAGE PROFICIENCY TEST AT CASEA OF MAKASSAR - Wahyu Ardiani (Publikasi dan UKI Press UKI Toraja., 2022)
This research is aimed to know the reading ability of Senior Air Traffic Control Cadets through ICAO English Language Proficiency Test. This research applied descriptive study. The population of the research was 87 cadets of D.III SATC CASEA Makassar which are divided into 4 classes, they are D.III SATC VI, D.III SATC VII, D.III SATC VIII A dan D.III SATC VIII B. The sample of the research took through their registration number consists of 24 cadets. They are cadets of D.III SATC VIII B. Procedure of collecting data that the researcher has applied was gave the reading test to cadets, and each cadet should answer the questions that given. The result of the research shows that the senior air traffic control cadets still have low ability in reading